Surface roughness of Carbides produced by abrasive water jet machining - Khan, Ahsan Ali; Awang, Mohd Efendee; Annuar, Ahmad Azwari (Asian Network for Scientific Information, 2005)
This study presents the effect of jet pressure, abrasive flow rate and work feed rate on smoothness of the surface produced by abrasive water jet machining of carbide of grade P25. Carbide of grade P25 is very hard and cannot he machined by conventional techniques. Cutting was perfonned on a water jet machine model W J 4080. The ab rasive used in investigations was garnet of mesh size 80. It was tried to cut carbide with low and medium level of abrasive flow rate, hut the jet failed to cut carbide since it is too hard and very high level of energy is required. Minimum rate of abrasive flow that made it possible to cut carbide efficiently was 135 g min-I . It was found from the investigations that with increase in jet pressure the surface becomes smoother due to higher kinetic energy of the abrasives. But the surface near the j et entrance is smoother and the surface gradually becomes rougher downwards and is the roughest near the jet exit. Increase in abrasive flow rate also makes the surface smoother which is due to the availability of higher number of cutting edges per unit area per unit time. Feed rate didn't show significant influence on the machined surface, but it was found that the surface roughness increases drastically near the jet entrance.